The Effect of Intellectual Capital on Financial Performance in Energy Sector Companies Listed on the Indonesian Stock Exchange (IDX) in 2020-2022 - Maryen Kartin Sarumaha; Manatap Berliana Lumban Gaol; Herti Diana Hutapea (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2024)
This study aims to determine how intellectual capital affects financial performance in energy sector companies listed on the Indonesian Stock Exchange (IDX) in 2020-2022. This study uses Financial Performance as an independent variable measured by Return On Asset (ROA) and uses Intellectual Capital (IC) as the dependent variable measured by Value Added Intellectual Coefficient (VAIC™) which consists of Value Added Human Capital (VAHU), Value Added Capital Employed (VACA), and Structural Capital Value Added (STVA). The theory used as the basis of this research is Resources-Based Theory (RBT) and supported by Knowledge-Based Theory. From the use of the purposive sampling method, 24 companies were obtained as samples and 72 observation data were used. The analytical tool used is SmartPLS with the Structural Equation Model (SEM). The hypothesis was analyzed from the results of bootstrapping in Path Coefficients which resulted in Intellectual Capital having a positive and significant effect on Financial Performance with a large effect obtained of 64.7%.